2019
DOI: 10.1111/apha.13256
|View full text |Cite
|
Sign up to set email alerts
|

Impaired butyrate absorption in the proximal colon, low serum butyrate and diminished central effects of butyrate on blood pressure in spontaneously hypertensive rats

Abstract: Aim Butyrate is a major gut microbiota‐derived metabolite. Reduced butyrate‐producing bacteria has been reported in the spontaneously hypertensive rat (SHR), a model of hypertension characterized by dysfunctional autonomic nervous system and gut dysbiosis. Here, we demonstrate a potential mechanism for butyrate in blood pressure regulation. Methods High‐performance liquid chromatography and liquid chromatography‐mass spectrometry were performed to measure butyrate levels in feces and serum. Ussing chamber dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 72 publications
(129 reference statements)
5
55
1
1
Order By: Relevance
“…6b). A recent study performed in SHR, showed the same antagonistic results, reporting higher fecal butyrate levels in contrast to circulation levels 40 . They also reported lower expression levels of butyrate-sensing receptors in the hypothalamus of SHR and reduced expression of Slc5a8 transporter in the colon, so they concluded that a reduced availability of serum butyrate in the SHR is possibly due to a diminished absorption in the colon.…”
Section: Scfa In Feces and Plasmamentioning
confidence: 55%
“…6b). A recent study performed in SHR, showed the same antagonistic results, reporting higher fecal butyrate levels in contrast to circulation levels 40 . They also reported lower expression levels of butyrate-sensing receptors in the hypothalamus of SHR and reduced expression of Slc5a8 transporter in the colon, so they concluded that a reduced availability of serum butyrate in the SHR is possibly due to a diminished absorption in the colon.…”
Section: Scfa In Feces and Plasmamentioning
confidence: 55%
“…Intriguingly, fecal SCFA concentrations in humans have been associated with higher blood pressure [ 30 ], while SCFA-producing microbiota are often associated with lower blood pressure [ 31 , 35 , 37 ]. Perhaps, increased SCFA availability in the intestines results in upregulation of absorption mechanisms, which could lead to relatively lower fecal concentrations and higher plasma availability, as was supported by a murine model [ 52 ]. There are no results from human intervention studies with SCFAs to target blood pressure.…”
Section: Gut Microbiota In Hypertensionmentioning
confidence: 99%
“…Papers published in Acta Physiologica provide prime examples for the use of BOLD MRI in these research areas. For instance, BOLD measurements in spontaneously hypertensive rats showed that the lack of gut microbiome‐derived butyrate influences the activity of cardio‐regulatory brain regions; this led to the hypothesis that microbial butyrate may play a role in blood pressure regulation 9 . In a rat model of ischemic stroke, dedicated functional MRI techniques were used in a longitudinal study to assess the benefit of early inhibition of the mitogen‐activated protein kinase 1/2 administered at a clinically relevant time point 10 .…”
mentioning
confidence: 99%
“…In a rat model of ischemic stroke, dedicated functional MRI techniques were used in a longitudinal study to assess the benefit of early inhibition of the mitogen‐activated protein kinase 1/2 administered at a clinically relevant time point 10 . As a non‐invasive technique, functional MRI complements various other ‘classical’ methods used to study cardiovascular control, ranging from—mostly invasive—in vivo to ex vivo techniques such as Ca ++ imaging 9,11,12 …”
mentioning
confidence: 99%